Kerajaan Jambi dan Pengaruh Islam - Arif Rahim (Universitas Batanghari Jambi, 2022)
This paper discusses the Jambi kingdom and its existence as a country located in international trade routes. This is interesting to study because its growth period coincided with the entry and development of Islam in the archipelago. Thus, this paper examines the influence of Islam on the Jambi Kingdom. By using a multi-dimensional approach and supported by the application of historical methods that refer to scientific history research procedures, the results of this study are expected to provide an explanation of the main problems proposed and so contribute to the development of science, especially about Jambi's local history. In addition, it can be used as material for consideration by related institutions in the context of preserving historical and cultural values and for regional development and development. The results showed that the Jambi kingdom was one of the archipelago's kingdoms that existed from the end of the 15th century to the early 20th century. This kingdom has received the influence of Islam since its inception. Putri Selaro Pinang Masak as the founder of the Jambi kingdom converted to Islam after marrying Ahmad Salim Datuk Paduka Berhalo, a person who came from Turkey and embraced Islam. Since then the Kingdom of Jambi has made Islam the official religion of the kingdom. In this case, the king has the position as head of state as well as religious leader. Orangkayo Hitam is a king who is directly involved with the spread of Islam. As a royal religion, Islam has an influence on royal institutions and people's lives in various aspects. In the political field, Islam influences the designation of the state, king, and the names of the ruling kings. The name of the kingdom changed to the sultanate. The king changed his name to Sultan. Meanwhile, the names of the kings changed from using words from Sankerta or Malay to using words in Arabic. State laws and regulations are now based on Islamic teachings. In the economic field, the influence of Islam can be seen in terms of trading procedures. The usury system is prohibited although in practice it is sometimes violated. In the social and cultural fields, the influence of Islam can be seen in the way of dress, as well as in social relations. Islamic prayers and the prophet's shalawat now strongly influence various ceremonies and arts.